Skilled Workforce Development and Industrialization in Nepal: Implications for Civic Order - Singh, Ayush Pratap; Jha, Abhas (International Research Journal of MMC, 2026)
This study aims to elaborate on how developing a skilled workforce accelerates a nation's economic valuation through industrialization, and how this transition fundamentally restructures society to establish civic order, focusing specifically on Nepal. To investigate this, a qualitative, desk-based research design was used. The research relies on secondary data sources, primarily utilizing industrial registration statistics from the Nepal Government’s Department of Industry, alongside international working papers from the Asian Development Bank, national policy reports, and broader academic literature. We analysed this information through a multi-disciplinary approach, synthesizing economic growth theories specifically Kaldor’s Growth Laws with sociological frameworks, and applied comparative case studies of developmental trajectories in East Asian economies. Our findings indicate that sustainable industrialization in agrarian economies like Nepal must initially rely on basic, labour-intensive manufacturing. However, Nepal currently faces an acute domestic skilled labour shortage, forcing a heavy reliance on foreign workers. Furthermore, the analysis reveals that industrialization acts as a societal architect; the necessity to manage a growing, urbanizing workforce directly drives the creation of modern civic institutions, such as public schooling and organized policing, to maintain social order. Ultimately, these findings imply that for successful modernization, Nepal must strategically prioritize labour-intensive manufacturing, heavily institutionalize technical and vocational education (TVET), and actively leverage industrial growth to strengthen the public institutions that sustain civic discipline.